A facile approach to hydrophilic, reverse zwitterionic, choline phosphate polymers. Issue 4 (7th November 2014) - Hu, Gaojie; Parelkar, Sangram S.; Emrick, Todd
Abstract : We describe a facile synthesis of an n -butyl substituted choline phosphate monomer (MBP), and its polymerization to afford polyMBP and its copolymers. PolyMBP provides access to water-soluble choline phosphate polymers that by cell culture analysis exhibit low toxicity and immunogenicity. Abstract : 2-{2-(Methacryloyloxy)ethyldimethylammonium}ethyl n -butyl phosphate (MBP) was synthesized and polymerized by controlled free radical methods to afford a new set of "reverse zwitterionic" choline phosphate (CP) substituted polymers. The synthesis overcomes prior limitations associated with related CP-methacrylates, affording facile access to MBP homopolymers and MBP-containing diblock copolymers. Dynamic light scattering revealed the size of polyMBP in water, while cell culture assays showed polyMBP to have excellent biocompatibility and non-immunogenicity. The facile synthesis of MBP monomer, and the corresponding polymers, opens a new platform towards a diverse set of functional, hydrophilic biocompatible polymers.